1998
DOI: 10.1002/(sici)1097-0029(19980601)41:5<393::aid-jemt6>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Origin and early development of Schwann cells

Abstract: Cellular events leading to the generation of Schwann cells from the neural crest have recently been clarified and it is now possible to outline a relatively simple model of the Schwann cell lineage in the rat and mouse. Neural crest cells have to undergo three main developmental transitions to become mature Schwann cells. These are the formation of Schwann cell precursors from crest cells, the formation of immature Schwann cells from precursors and, lastly, the postnatal and reversible generation of non‐myelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 98 publications
0
41
0
1
Order By: Relevance
“…NRG signaling is a key regulator of Schwann cell survival during the early stages of development via the PI3K͞Akt pathway (28,29). Given our observation that Cdk5 affects NRG͞ErbB signaling (5), we were interested to examine whether the integrity of Schwann cells, an integral component of the NMJ, was affected in Cdk5 Ϫ/Ϫ embryos.…”
Section: Number Of Large Achr Clusters Was Increased In Primary Musclementioning
confidence: 90%
See 1 more Smart Citation
“…NRG signaling is a key regulator of Schwann cell survival during the early stages of development via the PI3K͞Akt pathway (28,29). Given our observation that Cdk5 affects NRG͞ErbB signaling (5), we were interested to examine whether the integrity of Schwann cells, an integral component of the NMJ, was affected in Cdk5 Ϫ/Ϫ embryos.…”
Section: Number Of Large Achr Clusters Was Increased In Primary Musclementioning
confidence: 90%
“…4H), suggesting that the lack of S100 staining in Cdk5 Ϫ/Ϫ phrenic nerves was likely due to the loss of Schwann cells. Interestingly, the morphology and functions of these Schwann cells and their expression profiles of ErbB receptors are quite different from terminal Schwann cells (18,28,31). It is possible that the absence of defects in terminal Schwann cells of Cdk5 Ϫ/Ϫ embryos is, in part, because of their differential requirement of NRG͞ErbB signaling.…”
Section: B-d) Interestingly the Terminal Schwann Cells Remained Intmentioning
confidence: 99%
“…The response to IL6RIL6 of this cell population has been analyzed at the RNA level by RT-PCR and on gene arrays after 24 and 48 h of treatment. 3 We used viral particles containing the vector for C/EBP-␦-specific siRNAs to knockdown C/EBP-␦ mRNA. We used cells shortly after infection and found that knocking down C/EBP-␦ inhibited P0 mRNA expression.…”
Section: A 570 Nmmentioning
confidence: 64%
“…Treatment of such cells with IL6RIL6 increases P0 and C/EBP-␦ mRNA levels, as verified by RT-PCR and analysis on DNA-arrays. 3 In this system, the basal level of P0, and C/EBP-␦ mRNAs in the absence of IL6RIL6 is not negligible. To evaluate the role of C/EBP-␦ in P0 mRNA regulation in this system containing precursor glial cells, we infected the cells with viral particles containing pRS-C/EBP-␦2, and control pRS.…”
Section: C/ebp-␦ Down-regulates Pax3 and Mitf-mentioning
confidence: 99%
See 1 more Smart Citation